Specification for safety of household and similar electrical appliances Part 202. Particular requirements Sec 202.4. Spin extractors (BSI, 1990)
Requirements for extractors with a load capacity not exceeding 10 kg of dry textile matter and a container peripheral speed not exceeding 50 m/s. Also applies to spin extractors incorporated in electric washing machines. To be read in conjunction with BS 3456:Part 201